Theological Motifs in the Stories of the Qur’an - BAL, Samet Yahya (Scientific Journal of Faculty of Theology, 2022)
Anecdotes constitute an important sum within the integrity of the Qur'an. In addition, when the stories are compared with the other parts of the Qur'an, it is seen that they contain the same principles and subjects in terms of content. The stories in the Qur'an have been subjected to many evaluations in terms of moral, legal, fiqh and historical aspects in the context of accepting the reality and the existence of truth. The fact that the principles contained in the tales contain basic theological parameters brings to mind the reality of the tales and what kind of value they have in terms of theology. In the study, the points related to the belief in the Qur'anic anecdotes were emphasized and a theological view towards the stories was tried to be put forward.